Karakterisasi Molekular Fragmen Gen mexB Isolat Pseudomonas aeruginosa Multiresisten - Badaruddin, Fatmawaty; Supardi, Imam; Chatib Warsa, Usman; Soefie Retnoningrum, Debbie (Jurnal Kedokteran YARSI, 2008)
Antibiotics have been widely used in the treatment of infectious diseases. However, their effectiveness has been questioned due to the tendency of some bacterial resistance to antibiotics. Pseudomonas aeruginosa among others has been known to be resistant to several antibiotics due to its MexABOprM efflux pump. Perhaps, the nucleotide sequence of its mexB gene fragment has changed followed by changes in amino acid sequence leading to alteration of the substrate recognition site. This alteration causes disability of antibiotics to recognize it and they are pumped out from the bacterial cell causing decrease in its inhibition concentration. An observasional study was performed using four P. aeruginosa isolates (A,B,C and D) taken from four laboratories in Bandung, and the sensitivity test for several antibiotics (tetracyclin, ampicyllin, amoxicyllin-clavulanat, kanamycin, ciprofloxazin, trimetoprim-sulphametoxazol, chloramphenicol dan eritromycin), was performed using Kirby-Bauer method. The Minimum Inhibitory Concentrations (MICs) for 4 isolates were 20.57-39.07 mg/ml for erithromycin, 29.35-48.57 mg/ml for kanamycin, 30.35-68.75 mg/ml for tetracyclin, 45.57-97.50 mg/ml for ampicyllin, 23.69-97.50 mg/ml for chloramphenicol, 25.82-59.56 mg/ml for amoxcyllinclavulanat,21.88-79.00 mg/ml for trimetoprim sulphametoxazol, and 20.58-56.97 mg/ml for ciprofloxazin. The increasing of MIC to each antibiotic was shown for 4 isolates of P. aeruginosa multiresistant to several antibiotics being studied. PCR technique was used to detect mexB gene fragment asumed as the substrate recognition site. The percentage of homology between the nucleotide sequence of mexB multiresistant P. aeruginosa and mexB P. aeruginosa producing siderophore pioverdin (Acc. No. L11616, NCBI) showed 96%, 100%, 97%, and 96% homology for P. aeruginosa A,B,C and D respectively. Employing DNAstar program, fragment variant of mexB gene of 4 multiresistant isolates A, B, C and D was detected. This variation lead to amino acid substitution of Gly-417->Ser, Glu-417->Gln, Thr-424->Pro, Tyr-328->Phe, Asp-328->His for P. aeruginosa A,B,C and D respectively, along with the change of their secondary structure, that changed the functional protein of MexB.